Analisis Perbandingan Elastic Compute Service (ECS) Instance Alibaba Cloud Dengan Virtual Machine Azure - Ria Hefiana; Yusra Fernando (STMIK Budi Darma, 2024)
Cloud Computing is a development of computer networks or the internet, where the cloud image itself is taken from computer networks that can be abstracted from hidden complex infrastructure. By seeing the rapid growth in the use of cloud computing in Indonesia, the author feels it is important to conduct this research to provide the public with a better understanding regarding the choice of cloud platform that suits their needs.A comparative study of ECS Alibaba Cloud and Azure Virtual Machine was conducted to understand the differences between these two platforms. Seeing the many cloud users now in Indonesia, the author wants to do a comparative study between ECS Alibaba Cloud and Azure Virtual Machine. This research will consider Thread (users), Ramp-Up (Second), Loop Count and produce parameters Throughput, Latency, Simple Time/Response Time and look at Resource Utilization, CPU Utilization, Memory Utilization, Disk Utilization. Based on the test results between ECS Alibaba Cloud and Azure Virtual Machine, several conclusions were drawn, namely, the average Througput parameter results on Azure were 10,173/mbps and ECS 6,373/mbps. The results of the Sample Response Time parameter in Azure get a value of 16038/ms and ECS 22471.13/ms. The Latency Parameter results in Azure get a value of 14971.33/ms and ECS 19545.4/ms. Meanwhile the utilization results get an average value of Resource 2min 29sec, CPU 50.80%, Memory 35.05% and Disk 16.22% while for Alibaba Cloud ECS Utilization it gets an average value of Resource 2min 50 sec, CPU 57.85%, Memory 39.64% and Disk 12.28 %.